2017
DOI: 10.1021/acs.est.6b05462
|View full text |Cite
|
Sign up to set email alerts
|

Effect of E-waste Recycling on Urinary Metabolites of Organophosphate Flame Retardants and Plasticizers and Their Association with Oxidative Stress

Abstract: In this study, three chlorinated (Cl–mOPs) and five nonchlorinated (NCl–mOPs) organophosphate metabolites were determined in urine samples collected from participants living in an electronic waste (e-waste) dismantling area (n = 175) and two reference areas (rural, n = 29 and urban, n = 17) in southern China. Bis­(2-chloroethyl) phosphate [BCEP, geometric mean (GM): 0.72 ng/mL] was the most abundant Cl–mOP, and diphenyl phosphate (DPHP, 0.55 ng/mL) was the most abundant NCl–mOP. The GM concentrations of mOPs i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
57
2
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 135 publications
(63 citation statements)
references
References 47 publications
3
57
2
1
Order By: Relevance
“…In almost all available studies, di-ortho-cresyl phosphate (DoCP) and/or di-para-cresyl phosphate (DpCP) (determined alone or together) were detected only occasionally, and/or at relatively low levels (i.e. median levels <0.02 µg/l) in recent studies in China and USA, suggesting limited exposure to the precursors of these metabolites in these general populations (Schindler et al, 2013;Fromme et al, 2014;Kosarac et al, 2016;Lu et al, 2017;Romano et al, 2017;Chen et al, 2018;Ospina et al, 2018). However, higher frequencies were reported in some occupationally exposed populations (Jayatilaka et al, 2017, Tao et al, 2018.…”
Section: General Populationmentioning
confidence: 99%
See 2 more Smart Citations
“…In almost all available studies, di-ortho-cresyl phosphate (DoCP) and/or di-para-cresyl phosphate (DpCP) (determined alone or together) were detected only occasionally, and/or at relatively low levels (i.e. median levels <0.02 µg/l) in recent studies in China and USA, suggesting limited exposure to the precursors of these metabolites in these general populations (Schindler et al, 2013;Fromme et al, 2014;Kosarac et al, 2016;Lu et al, 2017;Romano et al, 2017;Chen et al, 2018;Ospina et al, 2018). However, higher frequencies were reported in some occupationally exposed populations (Jayatilaka et al, 2017, Tao et al, 2018.…”
Section: General Populationmentioning
confidence: 99%
“…This may be explained by differences in FR regulations, dietary habits, lifestyle, and use of PEFRs in household products and indoor environments (e.g., building material), between the various countries and/or study locations (Carignan et al, 2013;Butt et al, 2016;Lu et al, 2017;Chen et al, 2018;He et al, 2018b). Other factors were reported to have an impact on urinary PEFR metabolite concentrations, including timing (e.g., season of collection) (Hoffman et al, 2017a and b;Deziel et al, 2018;Ingle et al, 2018;Phillips et al, 2018), sex (e.g., women tend to have higher levels of DPHP than men, Hoffman et al, 2015b;Preston et al, 2017;He et al, 2018a;Ospina et al, 2018), behavior and activity patterns (e.g., hand washing and cleaning routines, nail painting) (Abdallah et al, 2016;Mendelsohn et al, 2016;He et al, 2018b) and age (Van den Lu et al, 2017;He et al, 2018a;Ospina et al, 2018;Sun et al, 2018). Urinary concentrations of the main PEFR metabolites were generally higher in toddlers than in adults (Butt et al, 2014 andCequier et al, 2015;Hoffman et al, 2015a;Van den Eede et al, 2015b;Chen et al, 2018;He et al, 2018a and b;Ospina et al, 2018).…”
Section: Possible Bias Limitations and Strengths Of The Reviewed Stumentioning
confidence: 99%
See 1 more Smart Citation
“…The effect of e-waste on urinary metabolites [15]. Decreased vaccine antibody titers following exposure to multiple metals and metalloids in e-waste exposed preschool children [11].…”
Section: Environmental Degradationmentioning
confidence: 99%
“…Some of the emerging OPEs has been included in the list of POPs, which can be rapidly degraded in the body to produce polar, hydrophilic metabolites and excreted through urine. Some studies have determined organophosphate metabolites in urine samples [4][5][6] . Lu et al [5] found Bis(2-chloroethyl) phosphate [BCEP] was the most abundant Cl-mOP, and diphenyl phosphate (DPHP, 0.55 ng/mL) was the most abundant NCl-mOP.…”
Section: Introductionmentioning
confidence: 99%